Synthesis of the Genome of Bacteriophage N4 - G. Yu. Fisunov; T. A. Semashko; D. V. Evsyutina; E. A. Tsoy; D. R. Kharrasov; K. S. Gumayunova; I. V. Tuchkov; K. A. Nikiforov; D. A. Rybal’chenko; V. V. Kutyrev; V. M. Govorun (Проблемы особо опасных инфекций, 2024)
At present, bacteriophages are considered as an alternative to antibiotics in prevention and treatment of bacterial infections, in particular cholera.The aim of the work was to demonstrate a method to obtain synthetic bacteriophage against Vibrio cholerae. Vibriophage N4 was selected as a subject for the study.Materials and methods. The genome sequence of vibriophage N4 (38.5 kb) was taken from the NCBI GenBank database. The sequence was divided into gene blocks of 1500–2000 bp. The gene blocks, in turn, were split into oligonucleotides. Sequence partitioning was carried out using the BAC-browser software that we have developed. Oligonucleotides were chemically synthesized; gene blocks were assembled from them. After that, the complete genome of vibriophage N4 was synthesized from the obtained gene blocks. The assembly of the synthetic genome took place in two stages. At the first stage, gene block cassettes of 5–7 pieces with sizes ranging from 7 to 10.5 thousand bp were generated via homologous recombination in yeast. The resulting cassettes were then amplified and used for in vitro assembly using 5’-3’ exonuclease and thermostable DNA polymerase. The resulting preparation was used for electroporation of V. cholerae cells.Results and discussion. The synthetic genome of vibriophage N4 was delivered into the V. cholerae strain M818 O1 biovar El Tor using electroporation. As a result, the formation of lytic plaques on the lawn of V. cholerae was observed. The range of technologies we have developed: software for assembly design, enzymes and buffers for the synthesis of gene blocks and their crosslinking by homologous recombination in vitro, the method for producing large-sized assemblies in yeast can be used to obtain artificial bacteriophages with a rational genome design.